Oral Pharmacokinetics of Hydroxycinnamic Acids: An Updated Review - Kleyton Santos Veras; Flávia Nathiely Silveira Fachel; Bibiana Verlindo de Araújo; Helder Ferreira Teixeira; Letícia Scherer Koester (MDPI AG, 2022)
Hydroxycinnamic acids (HCAs) such as caffeic acid (CA), chlorogenic acid (CGA), coumaric acid (COA) isomers, ferulic acid (FA) and rosmarinic acid (RA) are natural phenolic acids with widespread distribution in vegetal foods and well-documented pharmacological activities. However, the low bioavailability of HCAs impairs their administration by the oral route. The present review addresses new findings and important factors/obstacles for their oral administration, which were unexplored in the reviews published a decade ago concerning the bioavailability of phenolic acids. Based on this, the article aims to perform an updated review of the water solubility and gastrointestinal stability of HCAs, as well as describe their oral absorption, distribution, metabolism and excretion (ADME) processes by in vitro, ex vivo, in situ and in vivo methods.